Exploring Unitarism and Employer Resistance to Collective Bargaining in the public service in Botswana: Unitarism and Employer Resistance to Collective Bargaining in the public service - Bodilenyane, Keratilwe; Ukpere, Wilfred; Mabaso, Calvin (Journal of Economic Development, Environment and People, 2024)
The origins of collective bargaining in Botswana is relatively young. Compared to other African countries like South Africa and Zimbabwe, collective bargaining can be considered a late developer in Botswana. The government has been a dominant player for industrial relations in the public sector in Botswana. Unitary approach does not believe in third party intervention, such as trade unions. Trade unions are at best antagonists and impostors to matters that are a prerogative of the employer. The paper explores the unitary tendencies and employer resistance to collective bargaining. To realise this objective the paper adopted a social constructivism approach within a qualitative framework, to solicit people’s subjective views about the phenomenon of interest. The paper used a sample size of fifteen (15) participants from the public service and trade unions. Semi-structured interviews were used for data collection. The findings of the study revealed resistance to collective bargaining as demonstrated by several government unilateral decision-making tendencies. The study recommends that the government as the employer should accept a paradigm shift from a unilateral way of doing things and embrace collective bargaining as a genuine means for joint decision making.